2021
DOI: 10.48550/arxiv.2106.08962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient Deep Learning: A Survey on Making Deep Learning Models Smaller, Faster, and Better

Abstract: Deep Learning has revolutionized the fields of computer vision, natural language understanding, speech recognition, information retrieval and more. However, with the progressive improvements in deep learning models, their number of parameters, latency, resources required to train, etc. have all have increased significantly. Consequently, it has become important to pay attention to these footprint metrics of a model as well, not just its quality. We present and motivate the problem of efficiency in deep learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…Training and deploying large deep learning models is costly. For example, the cost of trying combinations of different hyper-parameters for a large model is computationally expensive and it highly relies on training resources [3]. The results of the average training time per epoch and the total training time are presented in Table 2.…”
Section: Training Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Training and deploying large deep learning models is costly. For example, the cost of trying combinations of different hyper-parameters for a large model is computationally expensive and it highly relies on training resources [3]. The results of the average training time per epoch and the total training time are presented in Table 2.…”
Section: Training Efficiencymentioning
confidence: 99%
“…Although there has been much effort on deep learning to improve the prediction accuracy of the state-of-the-art forecasting models, progressive improvements on benchmarks have been correlated with an increase in the number of parameters and the amount of training resources required to train the model, making it costly to train and deploy large deep learning models [3]. Therefore, a lightweight and training-efficient model is essential for fast delivery and deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Pruning [19,71,78,79,132,134,140,171,200,265,288] Quantization [19,68,90,134,166,179,291,307,311,314] Knowledge Distillation [29,41,42,80,83,88,95,170,186,195,220,228,231,239,257,266,267,274,295,296,300,312] Low rank factorization [76,98,119,168,190,196,210,292] Conditional Computation…”
Section: Model Compressionmentioning
confidence: 99%
“…Deep learning (DL) technologies have significantly advanced many fields critical to mobile applications, such as image understanding, speech recognition, and text translation [29,43,49]. Besides, a lot of research efforts have been put into optimizations of DL latency and efficiency [11,22,34,40], paving the path towards the local intelligent inference on mobile devices like smartphones. Recent study [8,45,51] indicates the intelligent Apps (iApps), smartphone Apps using in-App DL models, will be increasingly popular, which is also verified by our own study shown in Section 6.1.…”
Section: Introductionmentioning
confidence: 99%